Condiciones del entorno institucional y percepción de sobrecarga laboral del enfermero de cuidados críticos en un hospital de tercer nivel del Minsa Iquitos 2022 - Salas Noriega, Patriana (2024)
The objective was to determine the relationship that exists between the conditions of the institutional environment and the perception of work overload of the critical care nurse in a tertiary hospital of the MINSA Iquitos 2022. The method was quantitative and the design was descriptive, correlational and transversal. The population and sample consisted of 55 nurses from the critical care units of the Emergency, Medicine, Surgery, Pediatrics and neonatology services of the Loreto Regional Hospital. The technique was the survey and the instruments were the Critical Care Nurse Institutional Work Environment Condition Questionnaire and the Critical Care Nurse Work Overload Questionnaire. For the correlation analysis, the non-parametric inferential statistical test Chi Square (x2) was used, with df = 1 with < 0.05. The results were: 45.5% (25) were between 36 and 45 years old, 89.1% (49) were female, 47.2% (26) were specialists, 49.1% (27) were ) had more than 10 years of service in the institution and 96.4% had a rotating shift, from the Institutional Environment, 61.8% (34) stated that they had a “bad” institutional environment, from the Perception of work overload, the 94.5% (52) perceived “medium” work overload. In conclusion, it was demonstrated that there is a relationship between the institutional environment and the perception of work overload ( 0.409 (p=0.002)). Likewise, regarding the dimensions in the variables, it was found that environmental conditions had a greater impact on the institutional environment (0.992) and for work overload, a greater effect of the mental aspect was found (0.831).